2010
DOI: 10.1002/app.32602
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, intermolecular motion, and thermal properties of thiodiphenyl epoxy

Abstract: The thiodiphenyl epoxy (THEP) was prepared by the 4,4 0 -thiodiphenol (THDOL) and the epichlorohydrin (ECH) without using any NaOH or KOH catalysts. The THEP possessed weak hydrogen bonding in the cured THEP/DGEBA system. The intermolecular motion parameters k and q were 0.26 and À168.5, respectively, which determined by the Gordon-Taylor and Kwei equations. The soft sulfide linkage (ASA) of the THEP degraded at lower temperature than cured DGEBA material, and further to form various thermal stable sulfate der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Furthermore, there are comparatively few studies in the literature on the use of sulphur in epoxy resins despite some evidence of improved adhesion 14 and thermal stability. 15 It is more common, however, that sulphur-containing mercaptan resins are used as hardeners 16,17 in epoxy resin systems where the rapid curing at low temperature and excellent fluid resistance makes them ideal sealants. Sulphur-containing amino acid hardeners have also been used recently as a replacement for less environmentally friendly curing agents 18 that exhibit promising behaviour because thermal stability is unaffected by their usage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are comparatively few studies in the literature on the use of sulphur in epoxy resins despite some evidence of improved adhesion 14 and thermal stability. 15 It is more common, however, that sulphur-containing mercaptan resins are used as hardeners 16,17 in epoxy resin systems where the rapid curing at low temperature and excellent fluid resistance makes them ideal sealants. Sulphur-containing amino acid hardeners have also been used recently as a replacement for less environmentally friendly curing agents 18 that exhibit promising behaviour because thermal stability is unaffected by their usage.…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR spectrum of EPS (Figure 2) features a strong absorption peak at 914 cm −1 , which we assign to the epoxy group, and peaks at 1,029 and 1,244 cm −1 , which we assign to C-O-C. The absorption peak for C-S is observed at 1,174 cm −1 [38][39][40]. These results indicate that the synthesized product was a sulfur-containing EPS.…”
Section: Resultsmentioning
confidence: 74%
“…When comparing the two diols 4a and 4b , it can be observed that the diol THIO-ISOH retained higher weight than BPA-ISOH at temperature higher than 400 °C in nitrogen and 450 °C in air; also the char residue at high temperature (600 °C) was higher for THIO-ISOH than BPA-ISOH. This could be ascribed to a greater promotion of char formation by the sulphur in THIO-ISOH, which hindered the formation of volatile degradation products [ 28 ]; in air sulphur could also provide an additional protection at high temperature in the form of sulfate [ 43 ].…”
Section: Resultsmentioning
confidence: 99%